2014
DOI: 10.5194/hess-18-2343-2014
|View full text |Cite
|
Sign up to set email alerts
|

The suitability of remotely sensed soil moisture for improving operational flood forecasting

Abstract: Abstract. We evaluate the added value of assimilated remotely sensed soil moisture for the European Flood Awareness System (EFAS) and its potential to improve the prediction of the timing and height of the flood peak and low flows. EFAS is an operational flood forecasting system for Europe and uses a distributed hydrological model (LISFLOOD) for flood predictions with lead times of up to 10 days. For this study, satellite-derived soil moisture from ASCAT (Advanced SCATterometer), AMSR-E (Advanced Microwave Sca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(125 citation statements)
references
References 41 publications
5
110
0
1
Order By: Relevance
“…Adaptive localization is not only easily implemented in the ETKF, it also automatically ensures that the cross-process correlation is localized differently than the intra-process correlation, making it particularly suitable for data assimilation in coupled surfacesubsurface models. Others have encountered the problem with cross-process correlation, notably Zupanski (2013), Li et al (2013) and Wanders et al (2014), although no definitive solution to the problem has been presented. Adaptive localization, such as the method applied in this study, may be one possible solution.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive localization is not only easily implemented in the ETKF, it also automatically ensures that the cross-process correlation is localized differently than the intra-process correlation, making it particularly suitable for data assimilation in coupled surfacesubsurface models. Others have encountered the problem with cross-process correlation, notably Zupanski (2013), Li et al (2013) and Wanders et al (2014), although no definitive solution to the problem has been presented. Adaptive localization, such as the method applied in this study, may be one possible solution.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have already shown that this rainfall product does not perform well everywhere (Ward et al, 2011;Thiemig et al, 2012).…”
Section: Satellite Rainfall Productsmentioning
confidence: 99%
“…More recently, Wanders et al (2014) and Lievens et al (2015) assimilated the Soil Moisture Ocean Salinity (SMOS) soil moisture product into hydrological models. The first study assessed the impact of the joint assimilation of remotely sensed soil moisture (ASCAT (Advanced SCATterometer), AMSR-E (Advanced Microwave Scanning Radiometer -Earth observing system) and SMOS (Soil Moisture and Ocean Salinity)) on the flood predictions over the upper Danube basin using the distributed hydrological LIS-FLOOD model for operational services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional water management can benefit from timely and reliable information about soil moisture content: it can improve quantifications of flood risks by its effect on rainfall estimations and streamflow predictions (Beck et al, 2009;Massari et al, 2014;Wanders et al, 2014) and negative anomalies to current plant water demands are an indicator of (the onset of) droughts (CarrĂŁo et al, 2016;Wilhite and Glantz, 1985). The agricultural sector depends on sufficient root zone soil water availability for crop growth, while excess of soil water leads to severe losses (Feddes et al, 1978).…”
Section: Introductionmentioning
confidence: 99%